Stable hemiaminals from axially chiral pyridine compounds - ERDEM, SAFİYE (My University, 2023)
© 2023 Wiley Periodicals LLC.In this study, we have synthesized a series of 3-(pyridin-2-yl)-2-(pyridin-2-ylimino)thiazolidin-4-ol derivatives regioselectively from 2-iminothiazolidin-4-ones using LiAlH4 at room temperature. Due to the presence of the restricted rotation around the N3-Caryl single bond, the formation of M/P isomers was observed. The OH group of the hemiaminal was found to orient itself on the same side with pyridyl nitrogen during this restricted rotation to form an intramolecular hydrogen bond, which was demonstrated by the computational DFT study. This orientation presumably inhibited the occurrence of dehydration and stabilized the molecule.
Keywords: Temel Eczacılık Bilimleri; Eczacılık; Kimya Mühendisliği ve Teknolojisi; Yaşam Bilimleri; Moleküler Biyoloji ve Genetik; Sitogenetik; Kimya; Analitik Kimya; Biyokimya; Biyoinorganik Kimya; Fizikokimya; Spektroskopi; Sağlık Bilimleri; Temel Bilimler; Mühendislik ve Teknoloji; Basic Pharmaceutics Sciences; Pharmacology and Therapeutics; Chemical Engineering and Technology; Life Sciences; Molecular Biology and Genetics; Cytogenetic; Chemistry; Analytical Chemistry; Biochemistry; Bioinorganic Chemistry; Physical Chemistry; Spectroscopy; Health Sciences; Natural Sciences; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Temel Bilimler (SCI); Yaşam Bilimleri (LIFE); Mühendislik; Farmakoloji ve Toksikoloji; MÜHENDİSLİK, KİMYASAL; KİMYA, ANALİTİK; SPEKTROSKOPİ; KİMYA, ORGANİK; FARMAKOLOJİ VE ECZACILIK; BİYOKİMYA VE MOLEKÜLER BİYOLOJİ; Engineering, Computing & Technology (ENG); Natural Sciences (SCI); Life Sciences (LIFE); ENGINEERING; CHEMISTRY; PHARMACOLOGY & TOXICOLOGY; MOLECULAR BIOLOGY & GENETICS; ENGINEERING, CHEMICAL; CHEMISTRY, ANALYTICAL; SPECTROSCOPY; CHEMISTRY, ORGANIC; PHARMACOLOGY & PHARMACY; BIOCHEMISTRY & MOLECULAR BIOLOGY; Fizik Bilimleri; Kataliz; Farmakoloji; İlaç Keşfi; Organik Kimya; Physical Sciences; Catalysis; Pharmacology; Drug Discovery; Organic Chemistry; 2-iminothiazolidin-4-ol; axially chiral hemiaminal; intramolecular hydrogen bonding; pyridine compounds; stable hemiaminal; 2-iminothiazolidin-4-ol; axially chiral hemiaminal; intramolecular hydrogen bonding; pyridine compounds; stable hemiami